Climate Education Integration into Higher Learning Institutions (HLI) through Collaborative Action in Ethiopia - Belay, Berhanu; Ambaw, Gebermedihin; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Climate education is a vital tool for building community resilience, promoting adaptation, and mitigating the impacts of climate change. It empowers individuals to make informed, sustainable decisions and strengthens national climate action. AICCRA partners with 31 public universities, 19 ATVET colleges, and key ministries (Agriculture, Education, Labor & Skills), as well as international organizations such as UNESCO, GIZ, ICARDA, and RUFORUM. These partnerships, formalized through MoUs, support national strategies like the Climate Resilient Green Economy (CRGE) and the Home-Grown Economic Reform (HGER). AICCRA helped universities and colleges integrate Climate Knowledge Products (CKPs) through curriculum revisions, the creation of new programs, standalone climate courses, and customized short-term training modules. Four standardized modules, Climate Risk Management in Agriculture (CRMA), Agricultural Extension (CRMAE), Climate Smart Agriculture (CSA), and Climate Information Services (CIS), were developed to support both short courses and teaching at universities and technical colleges. Capacity building used a Training of Trainers (ToT) model, training 38 university faculty and 78 ATVET staff as master trainers who cascaded knowledge to 257 junior staff and over 23,000 community members in 69 districts. This resulted in improved soil and water conservation, land restoration, and stronger technical competencies among extension staff. Policy engagement led to the recommendation of a mandatory “Climate Basics” course for all first-year university students and the integration of climate content into major disciplines, particularly agriculture and health. Overall, AICCRA’s work is transforming higher education into a driver of climate literacy and resilience, helping build a more adaptive and sustainable Ethiopia.